Formulasi Sagun Bakar (Sabingurah) Tepung Beras Merah, Tepung Ubi Ungu, Tepung Bengkuang Sebagai Alternatif Snack Penderita Diabetes Melitus - Safyanti Safyanti; Nitta Isdiany; Nur Fauziah; Ummi Mahmudah (Jurnal Sehat Mandiri, 2024)
Diabetes mellitus can lead to severe complications, including neuropathy and death, due to uncontrolled blood glucose levels and worsening bodily conditions. Effective management of diabetes mellitus can be achieved through dietary regulation, particularly the consumption of complex carbohydrates with a low glycemic index and high fiber content. An innovative approach in diabetes management involves the development of snacks such as grilled Sagon, formulated with Red Rice Flour, Purple Sweet Potato Flour, and Jicama Flour (Sabingurah). The aim of this study was to evaluate the organoleptic properties and fiber content of this product. The research design was experimental, utilizing a completely randomized design (CRD) with three treatments, conducted at the Food Technology Laboratory, Department of Nutrition, Padang. The organoleptic properties were tested by 25 semi-trained panelists, and proximate analysis was performed at the BSPJI Laboratory in Padang. The results indicated no significant differences in the organoleptic quality regarding color (p=0.09), texture (p=0.067), and overall preference (p=0.209). However, significant differences were found in taste (p=0.00) and aroma (p=0.004), with the best formula being F3. The optimal weight for a single serving of Sabingurah was 46.25 grams (3 pieces), containing 170 kcal, 6.1 grams of protein, 6.5 grams of fat, 21.7 grams of carbohydrates, and 2.5 grams of fiber. The selling price for the best Sabingurah product per serving is IDR 5,500. Future research is recommended to assess consumer acceptability, shelf life, and further improvements in the formulation, particularly regarding fat content.